PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOTOR MATIC HONDA BEAT DIMASA PANDEMI COVID-19 (STUDY KASUS PADA DEALER HONDA PRIMA MOTOR ) - Yulianti, Aulia (Journal of Fundamental Management (JFM), 2023)
The thesis entitled "The Influence of Product Quality, Price, and Promotion on Purchase Decisions for Honda Beat Matic Motorcycles During the Covid 19 Pandemic" is the result of quantitative research that aims to answer questions about the Influence of Product Quality, Price, and Promotion on Purchase Decisions on Matic Motorcycles. Honda Beat. The population in this study is addressed to buyers of Matic Honda Beat Motorcycles at Honda Prima Dealers. All populations are included in the research subject with a total of 125 people. Methods of data collection using a survey method, with a questionnaire research instrument. Data analysis method using SmartPLS (Partial Least Square). This study proves that Product Quality has a positive and significant effect on Purchase Decisions, Price has a positive and significant effect on Purchase Decisions, and Promotion has a positive and significant effect on Purchase Decisions during the Covid 19 Pandemic. Based on the Original Sample Estimate value, Product Quality is 0.235, Price 0.355, Promotion 0.348 with a significant under 0.5%.